The Hostages of the Northmen : From the Viking Age to the Middle Ages (2019)
"The aim of this book is to investigate the taking and giving of hostages in peace processes during the Viking Age and early Middle Ages in Scandinavia and adjacent areas. Scandinavia has been absent in previous research about hostages from the perspectives of legal and social history, which has mostly focused on Antiquity (the Roman Empire), Continental Germanic cultures, such as the Merovingian realm, and Anglo-Saxon England. The examples presented are from confrontations between Scandinavians and other peoples in which the hostage giving and taking was displayed as a ritual act and thus became symbolically important. Hostages were a vital part of the peace processes and used as resources by both sides in the ‘areas of communication’ within the ‘areas of confrontation’. Literary texts as well as runic inscriptions, picture stones, place names, and personal names are used as source material."